Intuitive Six-Degree-of-Freedom Human Interface Device for Human-Robot Interaction - Lee, Doohoe; Hwang, Jinhak; Jung, Dawoon; Koh, Je Sung; Do, Hyunmin; Kim, Uikyum (IEEE Transactions on Instrumentation and Measurement, 2024)
An intuitive communication method between humans and robots is required to realize efficient human-robot interaction (HRI). In this article, an intuitive human interface device (HID) for robotic applications is proposed for realizing HRI. The sensing principle and design of the device are mainly described. The device can detect six-degree-of-freedom displacements with six-axis force/torque (F/T). The device mainly consists of a handle, sensing part, and base frame. The sensing part was designed with the capacitance sensing principle using an eccentric arrangement of electrodes. For ease of use, the part was designed to mechanically limit deformation by applying a blocking mechanism. All the components of the device were built-in. The device was manufactured in the form of a joystick that could be easily operated by a human. Consequently, a calibration process was conducted using deep learning to assess the performance of the developed HID. Furthermore, using the developed HID, tasks were performed for direct interaction with a collaborative robot manipulator.
Keywords: Direct teachings; Human interface devices; Humans-robot interactions; Intuitive Human Interface; Intuitive human interface device; Robot sensing system; Sensitivity; Six axes force; Six degrees of freedom; Six-axis force/torque sensing; Torque sensing; Direct teaching; human-robot interaction (HRI); intuitive human interface device (HID); six-axis force/torque (F/T) sensing; six-degree-of-freedom